Long-term mortality benefit of CRT-D vs. CRT-P upgrade procedures from conventional devices without prior ventricular arrhythmias. (24th May 2021) - Schwertner, WR; Kosztin, A; Behon, A; Merkel, E; Kuthi, L; Veres, B; Tokodi, M; Kovacs, A; Osztheimer, I; Kiraly, Á; Geller, L; Merkely, B
Abstract: Funding Acknowledgements: Type of funding sources: Public grant(s) – National budget only. Main funding source(s): This work was supported by the ÚNKP-20-3-I New National Excellence Program if the Ministry for Innovation and Technology in Hungary, the National Research, Development, and Innovation Office of Hungary (NKFIA; NVKP_16-1-2016-0017 National Heart Program), and the Higher Education Institutional Excellence Program of the Ministry for Innovation and Technology in Hungary, within the framework of the Therapeutic Development thematic program of the Semmelweis University. This work was also supported by the Artificial Intelligence Research Filed Excellence Program of the National Research, Development and Innovation Office of the Ministry of Innovation and Technology in Hungary (TKP/ITM/NKFIH). The research was also financed by the Thematic Excellence Program (Tématerületi Kiválósági Program, 2020-4.1.1-TKP2020) of the Ministry for Innovation and Technology in Hungary, within the framework of the Bioimaging thematic program of the Semmelweis University. Background:  Cardiac Resynchronization Therapy (CRT) upgrade can reverse pacing-induced cardiomyopathy (PiCMP) and related major ventricular arrhythmias (MVA). However, there is a lack of data comparing mortality benefit of adding an ICD to CRT during upgrade procedures in those without prior malignant ventricular arrhythmias (VAs). Purpose:  We aimed to compare the all-cause mortality, echocardiographic response, MVA occurrence and the rate of complications of patients with prior pacemakers (PM) upgraded to CRT-P or CRT-D devices.  Methods:  Between 2000-2018 patients who underwent a successful CRT upgrade procedure from conventional pacemaker without a prior MVAs were collected. From 270 patients 83 (30.7%) upgraded to CRT-D, 187 (69.3%) to CRT-P device. The primary endpoint was all-cause mortality, secondary endpoints were echocardiographic response defined as left ventricular ejection fraction (LVEF) increase ≥5%, the occurrence of subsequent MVAs and the rate of periprocedural complications. Results:  CRT-D upgrade patients were more likely to be males, have a favourable renal function and lower LVEF compared to CRT-P group. During the median follow-up time of 3.7 years, 25 (30%) CRT-D and 131 (70%) CRT-P upgrade patients reached the primary endpoint. By univariate analysis, CRT-D upgrade patients showed 45% (HR 0.55; 95%CI 0.38-0.78; p < 0.01) lower all-cause mortality risk than CRT-P group. By multivariate analysis CRT-D (HR 0.39; 95%CI 0.23-0.66; p < 0.01), male sex (HR 1.60; 95%CI 1.03-2.47; p = 0.04), LVEF (HR 0.97; 95%CI 0.94-0.99; p < 0.01) have confirmed as independent predictors of all-cause mortality. Assessing secondary endpoints, LVEF response (66% vs 63%; p = 0.72), MVA occurrence (3.4% vs 0.8%; p < 0.01) and the rate of periprocedural complications were comparable in the two groups (14.8% vs 7%; p = 0.87), despite the higher number of lead explantations during CRT-D procedures than CRT-P upgrade (13% vs 1%; p < 0.001). Conclusions:  Adding an ICD during CRT upgrade procedures showed 45% lower all-cause mortality risk than CRT-P alone in patients with a pacemaker and no previous ventricular arrhythmias. This beneficial effect was independent of the echocardiographic response, safety or subsequent ventricular arrhythmias.